Seven devils - Lam, Laura, 1988-; May, Elizabeth, 1987- (DAW Book collectors, 2020)
Eris has been assigned a new mission: to infiltrate a spaceship ferrying deadly cargo and return the intelligence gathered to the Resistance, but her partner for the mission, mechanic and hotshot pilot Cloelia, bears an old grudge against Eris, making an already difficult infiltration even more complicated.